(untitled) (Global Journal of Management and Business Research, 2012)
Labor-management relations are the interacting relations between labor and management. The purpose of our study is to find out the worker wage satisfaction, worker satisfaction with supervisory behavior and worker satisfaction with welfare items. This cross sectional study was conducted from October 2010 to January 2011. A group of 200 employees was take part in this study through a predesigned questionnaire which consists of three parts to meet the objectives, which was collected from private organizations. There is an dilemma of weak relationship between labor and management that the labor force is not satisfied with their management behavior, wages and welfare items. Which tends towards the lack of accuracy in products and process of producing products. By this research we come to conclusion that the government should took part in this segment to apply the labor law accurately to provide the rights to the labor force and management should also have to contribute their efforts to satisfy their labor force so that they can perform well when they were satisfied perfect. Its means that the management is the part of labor force and labor is the part of management. This relation can become strong when they provide satisfaction to each other in work place.